Sustainable beef cattle production: A comparative review between Australia and Indonesia - Latif, Amir; Koestoer, Raldi Hendro; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Beef cattle farming is an important production activity to meet the protein needs of the community. Livestock produces carbon emissions that contribute to increasing global warming. The purpose of this article is to discuss the conditions of Indonesian beef cattle farming compared to the beef cattle farming system in Australia. Method: The method used in writing this paper is the Systematic Literature Review (SLR) with bibliometric content analysis. We analyze related to